Construcción y validación de una escala para evaluar actitudes hacia personas de distinta clase social - Correa, Pablo (2024)
The objective of this work was to develop and validate a scale of attitudes towards people from different social classes in citizens of Gran Córdoba (Argentina) aged 18 to 65 years. A bank of 34 items was constructed and three identical versions were designed in which what varies is the evaluated group (high, middle or low class). The factor analysis showed a structure of two negatively correlated factors in the three versions of the scale. Specifically, one factor refers to positive emotions, beliefs and behaviors, while the other factor refers to negative emotions and beliefs towards people from different social classes. In addition, the results indicated adequate internal consistency for the three versions of the instrument.